Position specific peak running demands, and influence of bout type in professional rugby union - Daniel J. Glassbrook; Lewis D. Williams; Kevin J. McShane (PLoS ONE, 2025)
Objectives To quantify peak running intensity in professional rugby union across position groups, and peak running intensity differences between bout types (i.e., whole, starter, substitute). Design Longitudinal study. Method Global positioning systems were used to assess the activity of 36 professional rugby union players. A moving average approach was used to identify the 1- to 10-minute peak intensity period distances, and time spent above 80% and 90% of individual 1-minute match peak. Differences between position groups and bout type were determined by magnitude-based inferences. Results All position groups showed most likely moderate to most likely large differences in peak intensity periods, except for tight 5 vs. backrow (possibly trivial small and possibly small), and half-backs vs. outside backs (very likely trivial small to likely trivial small). No position group comparison for time spent above 80% and 90% of 1-minute match peak resulted in moderate or greater differences. Possibly moderate to most likely moderate difference were observed between forwards whole vs. forward substitutes in 2- to 10-minute peak periods; most likely moderate differences were observed between forwards starters vs. forward substitutes in 10-minute peak intensity period; and most likely moderate differences were observed between backs whole vs. backs substitutes in the 1-minute peak intensity period. For time spent above 80% and 90% of 1-minute match peak all bout type comparisons resulted in most likely moderate to most likely large differences. Conclusions There are meaningful differences between position groups in peak running intensity in professional rugby union, and substitute players perform lower peak intensity running than whole or starters.